Role and development of GLP-1 receptor agonists in the management of diabetes - Chee W Chia (Dove Medical Press, 2009)
Chee W Chia, Josephine M EganNational Institutes of Health, National Institute on Aging, Intramural Research Program, Baltimore, Maryland, USAAbstract: Glucagon-like peptide-1 (GLP-1) is a hormone secreted from enteroendocrine L cells of the intestine in response to food. Exogenous GLP-1 administration at pharmacological doses results in many effects that are beneficial for treating type 2 diabetes, these include: (1) an increase in insulin secretion from β cells; (2) a suppression of glucagon secretion from α cells in the presence of hyperglycemia but not hypoglycemia; (3) a delay in gastric emptying and gut motility which in turns delays absorption of ingested nutrients and dampens post-prandial glucose excursion; and (4) an increase in the duration of postprandial satiety therefore suppressing appetite and decreasing food intake which eventually leads to weight loss. However, GLP-1 is subject to rapid enzymatic degradation, and therefore, not suitable for long-term treatment. A synthetic enzyme-resistant GLP-1 receptor agonist that reproduces the biological effects of GLP-1 is in use and more are under development. This review aims at providing a summary of the properties of GLP-1 and the development of GLP-1-based therapies for treatment of diabetes.Keywords: incretin, GLP-1, GLP-1R agonist, diabetes